Therapeutic outcomes evaluation of adjuvant hyperbaric oxygen therapy for non-healing diabetic foot ulcers among sudanese patients - Fadol, Ethar Mohamedalfatih; Suliman, Hayat Mohamed; Osman, Bashier; Abdalla, Safa A.; Osman, Wadah J.A.; Mohamed, Elwasila M.; Abdoon, Iman Hassan (Diabetes & metabolic syndrome clinical research & reviews, 2021)
Diabetic foot ulcers (DFUs) are common complications of diabetes that frequently lead to amputation and disability. Despite some promising results in using hyperbaric oxygen therapy (HBOT) for DFUs treatment, its efficacy is still debatable. The aim of this study was to evaluate the therapeutic outcomes of adjuvant HBOT in non-healing DFUs treatment. A descriptive, retrospective, hospital-based study was conducted at Al–Mo'alem Medical City-Khartoum, Sudan from August to December 2018. Medical records of Type 2 diabetic patients, treated with HBOT plus standard wound care for DFUs, were included in the study. Data were analyzed by simple descriptive statistics and logistic regression. P ≤ 0.05 was considered statistically significant. The study results showed that 51.7% of patients had Wagner grade-3 ulcers and 28.3% had complete loss of protective sensation. Almost 61% of patients achieved complete ulcer healing while 16.7% underwent amputation. Twenty percent of patients treated with HBOT experienced ear barotraumas as adverse effects. Protective sensation (OR = 6.00, 95% CI = 1.79–20.16, p = 0.004) and more sessions of HBOT (OR = 17.35, 95% CI = 4.51–66.73, p = 0.000) were positive predictors of complete ulcer healing. Loss of protective sensation (OR = 0.17, 95% CI = 0.05–0.63, p = 0.007) was an indicator of amputation. Treatment with adjuvant HBOT enhanced ulcer healing and reduced amputation rate in patients with non-healing DFUs. HBOT could be considered a relatively safe intervention. Adjunctive hyperbaric oxygen therapy (HBOT) improves ulcer healing in patient with non-healing diabetic foot ulcers (DFUs)HBOT reduces the risk of amputation in patients with chronic DFUsThe presence of protective sensation and the greater number of HBOT sessions are positive predictors of complete ulcer healingAmputation is positively associated with peripheral neuropathy in patients with refractory DFUs